The women who raised me : a memoir - Rowell, Victoria (New York : William Morrow, 2007)
The actress and dancer describes her origins as a mixed-race child from the Maine foster care system, her efforts to build her career, and the remarkable women who supported and inspired her.
Keywords: Rowell, Victoria; Actors -- United States -- Biography; Dancers -- United States -- Biography; Foster children -- United States -- Biography; Foster mothers -- United States -- Biography